Use of artificial intelligence as an instrument of evaluation after stroke: a scoping review based on international classification of functioning, disability and health concept AI applications for stroke evaluation - Luvizutto, Gustavo Jose; Silva, Gabrielly Fernanda; Nascimento, Monalisa Resende; Sousa Santos, Kelly Cristina; Appelt, Pablo Andrei; Moura Neto, Eduardo de; Souza, Juli Thomaz de [UNESP]; Wincker, Fernanda Cristina; Miranda, Luana Aparecida; Hamamoto Filho, Pedro Tadao; Souza, Luciane Aparecida Pascucci Sande de; Simoes, Rafael Plana [UNESP]; et al. (Taylor & Francis Ltd, 2021)
Introduction: To understand the current practices in stroke evaluation, the main clinical decision support system and artificial intelligence (AI) technologies need to be understood to assist the therapist in obtaining better insights about impairments and level of activity and participation in persons with stroke during rehabilitation. Methods: This scoping review maps the use of AI for the functional evaluation of persons with stroke; the context involves any setting of rehabilitation. Data were extracted from CENTRAL, MEDLINE, EMBASE, LILACS, CINAHL, PEDRO Web of Science, IEEE Xplore, AAAI Publications, ACM Digital Library, MathSciNet, and arXiv up to January 2021. The data obtained from the literature review were summarized in a single dataset in which each reference paper was considered as an instance, and the study characteristics were considered as attributes. The attributes used for the multiple correspondence analysis were publication year, study type, sample size, age, stroke phase, stroke type, functional status, AI type, and AI function. Results: Forty-four studies were included. The analysis showed that spasticity analysis based on ML techniques was used for the cases of stroke with moderate functional status. The techniques of deep learning and pressure sensors were used for gait analysis. Machine learning techniques and algorithms were used for upper limb and reaching analyses. The inertial measurement unit technique was applied in studies where the functional status was between mild and severe. The fuzzy logic technique was used for activity classifiers. Conclusion: The prevailing research themes demonstrated the growing utility of AI algorithms for stroke evaluation.
Keywords: Stroke; artificial intelligence; machine learning; rehabilitation